Physical Rehabilitation of Paralysed Facial Muscles: Functional and Morphological Correlates - Angelov, Doychin N.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Using a combined morpho-functional approach the author found that polyinnervation of the neuro-muscular juction (NMJ) is the critical factor for recovery of function after transection and suture of the facial nerve. Since polyinnervation is activity-dependent and can be manipulated, the author tried to design a clinically feasible therapy by electrical stimulation or by soft tissue massage. First, electrical stimulation was applied to the transected facial nerve or to paralysed facial muscles. Both procedures did not improve vibrissal motor performance (video-based motion analysis of whisking), failed to diminish polyinnervation and even reduced the number of innervated NMJ to one fifth of normal values. In contrast, gentle stroking of the paralysed vibrissal muscles by hand resulted in full recovery of whisking. This manual stimulation depends on intact sensory supply of the denervated muscle targets and is also effective after hypoglossal-facial anastomosis, after interpositional nerve grafting, when applied to the orbicularis oculi muscle and after transection and suture of the hypoglossal nerve. From these results the author concludes that manual stimulation is a non-invasive procedure with immediate potential for clinical rehabilitation following facial nerve reconstruction.
Factors limiting motor recovery after peripheral nerve injury -- Attempts to improve axonal pathfinding and quality of target reinnervation -- Efforts to reduce collateral axonal branching at the lesion site -- Efforts to reduce intramuscular axonal sprouting in denervated muscles -- Discussion -- Significance axonal branching at the lesion site -- Unsuccessful ways to reduce intramuscular axonal sprouting in denerved muscles -- Successful ways to reduce intramuscular axonal sprouting in paralysed muscles -- Unsuccessful manual stimulation of paralysed forearm muscles after MMA -- Conclusions -- Subject index.
Keywords: Medicine; Neurosciences; Biomedicine; Neurosciences